Treatment decision in a 4-year-old-boy with left ventricular outpouching after advanced hemodynamical flow evaluation with 4Dflow CMR: A case report - Lagerstrand, Kerstin; Svensson, Par-Arne; Andersson, Linnea; Synnergren, Mats; Öhman, Annika; Petersson, Magnus; Sunnegardh, Jan; Dangardt, Frida (Frontiers in Pediatrics, 2022)
Background: The present study presents a diagnostic course for characterization of a congenital left ventricular outpouching (LVO) in a 4-years old boy with severe neonatal heart failure, evaluating the added value of CMR 4Dflow. Case presentation: A boy, born at full term, presented with heart failure immediately after birth. Echocardiography showed dilated left ventricle with poor function and LVO, initially interpreted as an aneurysm. No infection, inflammation or other cause for heart failure was found. With intensive medical treatment, the heart function returned to normal, and eventually all medication was terminated. At follow-up, surgical treatment of the LVO was discussed but after CMR 4Dflow, thorough evaluation of function of the left ventricle as well as the LVO was possible and the LVO was determined a double-chambered left ventricle with good prognosis. Conclusions: The present case demonstrates the clinical usability of CMR 4Dflow for improved decision-making and risk assessment, revealing advanced hemodynamic flow patterns with no need for operation.